Philosophy of Islamic Education: The Conceptual Foundation of the Indonesian National Education System - Anis Afifah; Abd. Hafid (Institut Attanwir Bojonegoro, 2025)
This study analyzes the contribution of Islamic philosophy of education in strengthening the conceptual foundation of Indonesia’s national education system. The urgency of this research arises from moral degradation, the dominance of instrumentalist paradigms that focus merely on cognitive aspects, and the challenges of globalization that threaten humanistic values in education. Using a qualitative narrative literature review, this research explores classical and contemporary sources through three philosophical dimensions—ontology, epistemology, and axiology. The findings indicate that Islamic philosophy of education provides an integrative paradigm that harmonizes intellectual, spiritual, moral, and social aspects; rejects the dichotomy between religious and secular sciences; and emphasizes tauhid, ethics, and humanity as the foundation of education. These contributions are in line with the vision of Law No. 20 of 2003, Pancasila, and the 1945 Constitution, thereby enriching theoretical discourse while also offering practical guidance for curriculum development, policy-making, and educational practice in Indonesia.